2016
DOI: 10.1210/jc.2016-2911
|View full text |Cite
|
Sign up to set email alerts
|

ATLANTIC DIP: Insulin Therapy for women with IADPSG-diagnosed Gestational Diabetes Mellitus. Does it work?

Abstract: Insulin treatment of IADPSG-diagnosed GDM results in rates of macrosomia, LGA, SGA, and maternal hypertensive disorders similar to those of women with NGT. Although NICU admissions are greater in the GDM cohort, they are primarily for nonmedical reasons. Neonatal hypoglycemia and polyhydramnios remain greater among women with insulin-treated GDM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Since the new recommendation of the IADPSG, several studies reported that treatment based on the IADPSG criteria improved pregnancy outcomes. However, those studies were retrospective, and the comparison groups were women with normal glucose tolerance or GDM determined through different glucose cut-off values or diagnostic methods, such as 100 g OGTT [8][9][10]. A recent study reported that no differences were noted between untreated and treated patients diagnosed by the IADPSG criteria [11].…”
Section: Treatment Of Gestational Diabetes Diagnosed By the Iadpsg Crmentioning
confidence: 99%
“…Since the new recommendation of the IADPSG, several studies reported that treatment based on the IADPSG criteria improved pregnancy outcomes. However, those studies were retrospective, and the comparison groups were women with normal glucose tolerance or GDM determined through different glucose cut-off values or diagnostic methods, such as 100 g OGTT [8][9][10]. A recent study reported that no differences were noted between untreated and treated patients diagnosed by the IADPSG criteria [11].…”
Section: Treatment Of Gestational Diabetes Diagnosed By the Iadpsg Crmentioning
confidence: 99%
“…Thus, there is need for improved targeted interventions that have been shown to be of benefit, such as intensified treatment 14 or screening for gestational hyperglycaemia in the first trimester, that is advised by some groups and guidelines 4, 13 . Facilitating and improving national birth registries could also assist us in answering the unresolved points addressed here.…”
Section: Resultsmentioning
confidence: 99%
“…before typical time for OGTT testing, are usually considered as more glucose intolerant than those with onset at gestational week 24-28 or later 13 . The influence of overweight in women with GDM varies, but women with high BMI before pregnancy are overrepresented in most GDM cohorts 14,15 . Both MODY and type 1 diabetes may become manifest during pregnancy 16 , which adds to the complexity of diagnosing and treating hyperglycaemia in pregnancy.…”
mentioning
confidence: 99%
“…It is also interesting to explore the cross-talk between GDM and these conditions at the protein level. Finally, many studies also found that the treatment of GDM patients did not significantly reduce some of the maternal and fetal outcomes such as subsequent diabetes, metabolic syndrome, perinatal death, neonatal hypoglycemia, and childhood obesity [ 13 , 75 77 ]. Thus, it is necessary to develop prognostic markers for postpartum and long-term outcomes in treated patients.…”
Section: Considerations and Recommendations For Future Studiesmentioning
confidence: 99%
“…Moreover, current treatments may have limited effects on early GDM (diagnosed in high-risk women at <24 weeks of gestation) [12]. A recent study also showed that the incidences of neonatal hypoglycemia and polyhydramnios remain high after insulin treatment [13]. Thus, GDM has become a serious public health problem that increases health care costs during and post pregnancy [14].…”
Section: Introductionmentioning
confidence: 99%